Evaluation of the educational environment of the Saudi family medicine residency training program - Abdullah T Khoja (Wolters Kluwer Medknow Publications, 2015)
Objectives: The study was conducted to evaluate the educational environment (EE) in Family Medicine Training Programs. Materials and Methods: A cross-sectional survey, The Postgraduate Hospital Educational Environment Measure (PHEEM), was distributed to all residents at the four training centers in the central region. Cronbach's alpha was used to test the reliability. The mean and standard deviation (SD) for each item, the overall score and the three domains were calculated. A multiple linear regression model was developed with PHEEM scores as an outcome. The Mann-Whitney-Wilcoxon test was used to compare each item based on the selected factors. Results: The overall score was 67.1/160 (SD: 20.1). The PHEEM's domains scores: 24.2/56 (SD: 7.13) for perception of role autonomy; 25.3/60 (SD: 8.88), for perception of teaching; and 17/44 (SD: 5.6), for perception of social support. Training center and Level of training were the significant outcome predictors. Centre 1 (Joint Program) significantly had better scores than Centre 2. The instrument showed great reliability with a Cronbach's alpha of 0.92. Conclusions: There are many problems in the training program. Urgent actions are needed to improve the residents' learning experience particularly during rotations. Also, the curriculum should be restructured, and effective training methods introduced using the Best Evidence in Medical Education to meet the expectations and learning needs of family physicians.